Determining the thermal-physical characteristics of a coke foam layer in the fire protection of cable articles with foaming coating - Tsapko, Yuriy; Likhnyovskyi, Ruslan; Tsapko Аleksii; Kovalenko, Vitalii; Slutska, Oksana; Illiuchenko, Pavlo; Kravchenko, Rostyslav; Sukhanevych, Maryna (Eastern-European Journal of Enterprise Technologies, 2023)
An issue related to using cable products for building structures is to ensure their stability and durability when operating within wide limits. Therefore, the object of research was a change in the properties of the polymer sheath of the cable during the formation of a swollen coating layer under the influence of high temperature. It is proved that in the process of thermal action on the flame retardant coating, the process of thermal insulation of the cable involves the formation of particulate products on the surface of the sample. Under the action of the burner flame, a temperature was reached on the surface of the sample, which led to a swelling of the coating of more than 16 mm. The measured temperature on the inverse surface of the sample was no more than 160 °C, which indicates the formation of a barrier for temperature. In this regard, a calculation and experimental method for determining thermal conductivity when using a flame retardant as a coating has been developed, which makes it possible to estimate the coefficients of temperature conductivity and thermal conductivity under high-temperature action. According to the experimental data and established dependences, the coefficients of temperature conductivity and thermal conductivity of wood were calculated, which are 214.4·10–6 m2/s and 0.62 W/(m∙K), respectively, due to the formation of a heat-insulating swollen layer. The maximum possible temperature penetration through the thickness of the coating was assessed. A temperature was created on the surface of the sample, which significantly exceeds the ignition temperature of the polymer sheath of the cable, and, on a non-heated surface, does not exceed 160 °C. Thus, there is reason to argue about the possibility of directed adjustment of the fire protection processes of an electrical cable by using coatings capable of forming a protective layer on the surface of the material, which inhibits the rate of heat transfer.